Assessment of toxic metals in water and sediment of Pasur River in Bangladesh - Ali, Mir Mohammad; Ali, Mohammad Lokman; Islam, Md. Saiful; Rahman, Md. Zillur (IWA Publishing, 2018)
This study was conducted to assess the levels of toxic metals like arsenic (As), chromium (Cr), cadmium (Cd), and lead (Pb) in water and sediments of the Pasur River in Bangladesh. The ranges of Cr, As, Cd, Pb in water were 25.76-77.39, 2.76-16.73, 0.42-2.98 and 12.69-42.67 μg/L and in sediments were 20.67-83.70, 3.15-19.97, 0.39-3.17 and 7.34-55.32 mg/kg. The level of studied metals in water samples exceeded the safe limits of drinking water, indicating that water from this river is not safe for drinking and cooking. Certain indices, including pollution load index (PLI) and contamination factor (Ci f) were used to assess the ecological risk. The PLI indicated progressive deterioration of sediments by the studied metals. Potential ecological risks of metals in sediment indicated low to considerable risk. However, the Ci f values of Cd ranged from 0.86 to 8.37 revealed that the examined sediments were strongly impacted by Cd. Considering the severity of potential ecological risk (PER) for single metal (Ei r), the descending order of contaminants was Cd >Pb> As> Cr. According the results, some treatment scheme must formulate and implement by the researchers and related management organizations to save the Pasur River from metals contamination.